Transcaruncular Medial Canthal Tendon Plication with Lower Eyelid Suture Sling in Facial Nerve Palsy. (24th February 2014) - Sira, Mano; Norris, Jonathan H.; Nduka, Charles; Malhotra, Raman
Abstract: Purpose : To report a technique for correcting lower eyelid punctal ectropion with an inferiorly displaced or retracted medial eyelid due to facial nerve palsy, by extending a suture sling along the pre-tarsal lower eyelid when performing transcaruncular medial canthal tendon plication. Methods : Single-centre retrospective, non-comparative review of patients with facial nerve palsy who underwent medial canthal tendon plication with lower eyelid suture sling (MCT suture sling). Outcome measures included: the presence of lower eyelid ectropion, medial eyelid height, punctal position, inferior marginal reflex distance (MRD) and inferior scleral show measured both pre-operatively and at the last follow-up visit. Results : Thirty-three patients with facial nerve palsy with a mean age of 59, underwent MCT suture sling for lagophthalmos and/or ectropion. Then, 66% (21/32) of cases had punctal ectropion pre-operatively and 9% (3/32) had punctal ectropion at the last follow-up. Medial eyelid height was deemed to improve in 66% (21/32) of cases at the last follow up visit. Follow-up was mean 13.5 months. Six (18%) patients were deemed failures due to inferior MRD and inferior scleral showing worse than pre-operative measurements. Discussion : We report a technique for incorporating a suture sling to transcaruncular-approach MCT plication when the medial canthus has retracted or descended thus requiring support and a posterior vector. It avoids rounding of the medial canthal angle that may occur with traditional medial canthoplasty. Transcaruncular MCT plication is well described. Incorporating a suture sling to potentially reduce single point-fixation cheese-wiring and early dehiscence is minimally invasive, non-excisional and repeatable.